Management of interdisciplinary project approaches in Engineering Education: a case study - Lima, Rui M. (2009)
This paper describes project management processes of coordination teams, in the implementation of interdisciplinary project approaches in Engineering Education. These interdisciplinary projects are based on the Project-Led Education (PLE) concept and are being implemented since 2004/2005 in the Industrial Management and Engineering (IME) master degree course (1st and 2nd cycle of Engineering Education) at University of Minho. Usually, these approaches involve a coordination team of 10 to 15 members with different roles: teachers, tutors and education researchers. This team is responsible for preparing the project for the semester and forming the students’ teams. The coordination of these two types of teams is centred on a project manager that is responsible for, and supports, all the work developed during the semester, e.g., prepare the initial presentation of the project to the students, prepare the web site that supports the work, establish the communication between students and the rest of the team, prepare the students’ guide, and so on. Managing these projects is an intense task that demands a lot of time and different competencies. In this work it is presented a project management framework based on project management knowledge areas, to aid coordination teams to achieve better results.